The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.brat.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy for insomnia in alcohol dependent patients: A randomized controlled pilot trial

Abstract: In a randomized controlled trial, we evaluated the efficacy of cognitive-behavioral treatment for insomnia to improve sleep and daytime symptoms, and to reduce relapse in recovering alcohol dependent (AD) participants. Seventeen abstinent AD patients with insomnia (6 women, mean age 46.2 ± 10.1 years) were randomized to 8 sessions of cognitive behavioral treatment for insomnia for AD (CBTI-AD, n=9) or to a behavioral placebo treatment (BPT, n=8). Subjective measures of sleep, daytime consequences of insomnia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 32 publications
4
103
3
2
Order By: Relevance
“…Commonly reported phenomena include shortened sleep onset latency (MacLean and Cairns 1982; Roehrs et al 1999; Williams, MacLean, and Cairns 1983; Stone 1980; Scrima et al 1982) and increased SWS in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013; MacLean and Cairns 1982; Prinz et al. 1980; Feige et al 2006; Arnedt, Rohsenow, et al 2011). REM sleep is suppressed, with a longer latency to REM sleep and decreased REM sleep in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013) or across the whole night (Van Reen, Jenni, and Carskadon 2006; Williams, MacLean, and Cairns 1983; Roehrs et al 1999; Rundell et al 1972; Roehrs, Yoon, and Roth 1991; Arnedt, Rohsenow, et al 2011).…”
Section: 0 Acute Effects Of Alcohol On Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly reported phenomena include shortened sleep onset latency (MacLean and Cairns 1982; Roehrs et al 1999; Williams, MacLean, and Cairns 1983; Stone 1980; Scrima et al 1982) and increased SWS in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013; MacLean and Cairns 1982; Prinz et al. 1980; Feige et al 2006; Arnedt, Rohsenow, et al 2011). REM sleep is suppressed, with a longer latency to REM sleep and decreased REM sleep in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013) or across the whole night (Van Reen, Jenni, and Carskadon 2006; Williams, MacLean, and Cairns 1983; Roehrs et al 1999; Rundell et al 1972; Roehrs, Yoon, and Roth 1991; Arnedt, Rohsenow, et al 2011).…”
Section: 0 Acute Effects Of Alcohol On Sleepmentioning
confidence: 99%
“…1980; Feige et al 2006; Arnedt, Rohsenow, et al 2011). REM sleep is suppressed, with a longer latency to REM sleep and decreased REM sleep in the first half of the night (Williams, MacLean, and Cairns 1983; Van Reen, Jenni, and Carskadon 2006; Sagawa et al 2011; Rundell et al 1972; Chan et al 2013) or across the whole night (Van Reen, Jenni, and Carskadon 2006; Williams, MacLean, and Cairns 1983; Roehrs et al 1999; Rundell et al 1972; Roehrs, Yoon, and Roth 1991; Arnedt, Rohsenow, et al 2011). In the second half of the night, sleep is disrupted, with increased wakefulness and/or stage 1 sleep.…”
Section: 0 Acute Effects Of Alcohol On Sleepmentioning
confidence: 99%
“…7 Although there is a paucity of rigorous controlled designs, preliminary studies of CBTi in comorbid disorders have demonstrated positive outcomes for both sleep variables and clinical symptoms across a range of diagnoses, including depressive disorders, posttraumatic stress disorder, alcohol dependence, and psychosis. [17][18][19][20][21] Despite the burgeoning literature on mindfulness-based insomnia interventions, particularly in relation to chronic illness, 22,23 there is a dearth of evidence for psychological therapies for insomnia outside of CBTi, particularly in the context of comorbid psychiatric difficulties.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…The trial involved 60 abstinent patients with alcohol dependence, who were assigned to either a CBT-I condition with individual therapy sessions or a self-help condition, in which sleep problems were addressed by telephone support through a therapist, or a waiting list control condition (n = 20 each). In a similar vein, Arnedt et al observed in a pilot RCT, in which 17 abstinent patients with alcohol dependence received either eight sessions of CBT-I modified for alcohol dependence or a placebo treatment, a total relapse rate of 47 %, with no significant group differences [2].…”
Section: Alcohol Dependencementioning
confidence: 67%